The Utilization of Instagram Social Media on @Mistakeworld's Media Partners to Spreading News - Muriany, Jossy Andro; Adiansyah, Achmal Hakim; Khumayah, Siti; Erawati, Dedet (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the digital era, social media has become the main tool in disseminating information, including in the world of journalism and media partners. This study aims to analyze the use of Instagram by @Mistakeworld media partners in spreading news, especially in the music community in Cirebon. @Mistakeworld itself is an alternative media account to load activities for its members who like pop culture (Skate, Music, Graffiti, fashion etc.) around the Cirebon area. at first mistake world was Illegal Magazine which then changed its name in June 2023. the purpose of the establishment of mistake world was so that people in Cirebon in particular were not too dependent on Mainstream media. Using qualitative methods and New Media theory, this research examines how Instagram features such as Stories, Reels, and Feeds are used to build interactions with audiences. New Media The results show that Instagram is not only an information sharing platform, but also creates close connectivity between media partners, musicians, and their fans. High interactivity through comments, Direct Messages, and other features allow for wider and more responsive news dissemination.